Working Poor : Farmworkers in the United States - Griffith, David, 1951- (Book collections on Project MUSE., 1995)
Working Poor investigates the lives and working conditions of migrant farmworkers in seven regions of the United States. The community studies in this volume include descriptions and analyses of the low-income neighborhoods of Immokalee, Florida; Parlier, California; Weslaco, Texas; and Mayagüez, Puerto Rico, where growers and farm contractors put immigrants to work in fruit and vegetable harvests. The authors link farmworker communities that have winter growing seasons with summer labor supply demand regions in the northern United States, in particular south-western Michigan, N.